Improving Students’ Ability in Using Passive Voice through Discussion Method - Batari Rahma Syafina (Universitas Panca Sakti Bekasi, 2022)
Passive voice is one of the most important subjects in vocational English subjects. However, many of the students do not understand deeply about passive voice and few of them do not even understand the basic knowledge of passive voice. Therefore, the researcher tried to apply the group discussion method in the classroom so that students could work together to solve problems. The discussion method allows establishing a rapport with students, stimulating their critical thinking and articulating ideas clearly (McKeachie & Svinicki, 2006). The purpose of this journal is to examine various aspects of the discussion method of teaching in SMK Teknologi Nasional and its role in improving students' abilities in using passive voice. The results have shown that the students show progress in knowledge of passive voice and that the teacher is not the sole authority in class